The Effect of Financial Inclusion, Financial Literacy, Perceived Usefulness, and Perceived Ease of Use on Fintech Adoption among MSMEs - Bahrudi Efendi Damanik; Wendi Robiansyah (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The evolution of financial technology (fintech) has revolutionized transactional frameworks and enhanced accessibility to financial services, especially for Micro, Small, and Medium Enterprises (MSMEs). Nevertheless, the integration of fintech among MSMEs is still arguably restricted regardless of its prospective advantages. This investigation intends to evaluate the impact of financial inclusion, perceived usefulness, perceived ease of use, and financial literacy on fintech adoption. A quantitative explanatory research framework was utilized by surveying 100 MSME proprietors chosen via purposive sampling techniques. Data processing was conducted utilizing multiple linear regression analysis, validated by classical assumption assessments encompassing normality, multicollinearity, and heteroscedasticity diagnostics. The empirical outcomes indicate that financial inclusion, perceived usefulness, and perceived ease of use exert a positive and meaningful impact on fintech integration, whereas financial literacy demonstrates a negative and significant inverse effect. All independent variables substantially dictate fintech integration among MSMEs. This inquiry infers that fintech integration is determined by both technological assessments and financial competency dynamics. The ramifications suggest that bolstering digital financial competencies, refining intuitive fintech interfaces, and broadening financial accessibility constitute vital approaches to elevate fintech integration among MSMEs.